Kognitive Neurophysiologie des Menschen - Human cognitive neurophysiology Vol. 8 (2015) - (:unkn) unknown; Justus Liebig University Giessen (My University, 2015)
J. Wackermann: Dietrich Lehmann - A personal recollection H. Witte: Dietrich Lehmann - Doctor honoris causa of the Friedrich Schiller University Jena W. Skrandies: Dietrich Lehmann as a Neurophysiologist P.L. Faber, P. Milz, D. Lehmann: EEG of two persons during their roles as spiritual trance healer and as client - a pilot study M. Koukkou: EEG manifested brain functional states with state-dependent information processing: a short review of the concept from the sixties to today W. Skrandies: Abstracts of the 23rd German EEG/EP Mapping Meeting Announcements - Ankündigungen
Keywords: ddc:610